SHP-2 activates signaling of the nuclear factor of activated T cells to promote skeletal muscle growth - Fornaro, Mara (The Rockefeller University Press, 2006)
The formation of multinucleated myofibers is essential for the growth of skeletal muscle. The nuclear factor of activated T cells (NFAT) promotes skeletal muscle growth. How NFAT responds to changes in extracellular cues to regulate skeletal muscle growth remains to be fully defined. In this study, we demonstrate that mice containing a skeletal muscle–specific deletion of the tyrosine phosphatase SHP-2 (muscle creatine kinase [MCK]–SHP-2 null) exhibited a reduction in both myofiber size and type I slow myofiber number. We found that interleukin-4, an NFAT-regulated cytokine known to stimulate myofiber growth, was reduced in its expression in skeletal muscles of MCK–SHP-2–null mice. When SHP-2 was deleted during the differentiation of primary myoblasts, NFAT transcriptional activity and myotube multinucleation were impaired. Finally, SHP-2 coupled myotube multinucleation to an integrin-dependent pathway and activated NFAT by stimulating c-Src. Thus, SHP-2 transduces extracellular matrix stimuli to intracellular signaling pathways to promote skeletal muscle growth.